The Assessment of Ankle Range-of-Motion and Its Relationship with Overall Muscle Strength in a Cross-Section of Soccer Players - Piergiorgio Francia; Carlo Ferri Marini; Leonardo Bocchi; Barbara Piccini; Giuseppe Seghieri; Ario Federici; Sonia Toni; Francesco Lucertini (MDPI AG, 2023)
Soccer (football) practice can induce a limitation of ankle range of motion (ROM) that is a possible risk factor for injury and other negative consequences over time. The main objective of this research was to investigate the effects of soccer practice on ankle ROM throughout the entire period of a sports career of soccer players (SP). Furthermore, the relationship between ankle ROM and muscle strength in SP of different ages was studied. A total of 204 SP (range 6.7-45.1 years) and 87 controls (range: 7.5-45.2 years) matched for age, body mass index (BMI), and gender, were assessed. Ankle ROM in both plantar flexion (APF) and dorsiflexion (ADF) in addition to handgrip strength (HGS) were evaluated using an inclinometer and the Jamar hydraulic hand dynamometer, respectively. The comparison between SP and control groups showed a significant reduction in ankle ROM of both APF (26.3 ± 7.2° vs. 32.6 ± 7.4°; d = −0.90; p < 0.001) and ADF (95.5 ± 15.6° vs. 105.5 ± 15.8°; d = −0.66; p < 0.001). In SP, the results of the ANOVAs test indicate that age had a significant effect on ADF (F = 4.352, p = 0.038, partial eta-squared (ηp2) = 0.015) but not on APF (F = 0.430, p = 0.746, ηp2 = 0.001). Moreover, considering only the SP, a weak inverse correlation between ADF and HGS group ADF was found (rs = −0.27; p < 0.001). Factors such as the non-linear trend of growth in young SP could hinder the definition of the relationship between ankle ROM, age, and muscle strength. However, the appropriate consideration of age and muscle strength could facilitate the management of ankle ROM in PF of different ages.